A universal glass-induced method for the synthesis of cyano group modified g-C3N4 with excellent photocatalytic performance. (August 2022) - Chen, Mengyao; Zhang, Feng; Wei, Kaiying; Yu, Chunling; Wang, Xiuying; Song, Yu
Abstract: Cyano group modification has been demonstrated to be an effective approach to improve the photocatalytic performance of g-C3 N4 due to its ability to improve charge separation efficiency and enhance visible light response. So far, the commonly used methods for synthesizing cyano group modified g-C3 N4 (CCN) include multiple-step operations and are easy to cause corrosion of equipment and environmental pollution. In this paper, we developed a glass-induced method to prepare CCN, namely melamine/urea in a ceramic combustion boat covered with a glass slide was calcined and then CCN film/powder was generated on the glass slide. We found that this method is universal and irrespective of the raw material characteristics, and the content of cyano groups is related to the filling degree of the combustion boat. In addition, the CCN powder derived from the mixture of melamine and urea originally grown on the glass slide was very easy to detach from the glass slide due to its loose structure, and this powder exhibited excellent photocatalytic activity due to its large surface area and cyano group modification. This work puts forward an effective strategy to introduce cyano groups into g-C3 N4, and it would open the sights for further glass-induced modification. Graphical abstract: Image 1 Highlights: Cyano group modified g-C3 N4 was prepared via a universal glass-induced method. This method requires a closed reaction environment and a glass slide. Cyano group modified g-C3 N4 powder was only generated on the glass slide. Cyano group modified g-C3 N4 powder exhibited superior photocatalytic activity.